Affecting Structural Factors on the Entrepreneurship Behavior of the Academic Members of Healthcare - Rafat MOHEBIFAR; Azad SHOKRI; Sima RAFIEI; Negin MOHAMMADI; Maria MOHAMMADI; Sima MIRZAEI MOGHADAM (Tehran University of Medical Sciences, 2020)
Background: The study aimed to assess affecting structural factors on the entrepreneurship behavior of the academic members of healthcare in Qazvin University of Medical Sciences, Central Iran. Methods: This was a descriptive, cross-sectional study conducted among faculty members working in five faculties of Qazvin University of Medical Sciences, Iran in 2018. Data were collected using a three-part standard questionnaire including demographic characteristics, entrepreneurial behavior and structural factors questions. ANOVA and linear regression modeling were used in STATA software version 14. Results: Of 270 academic staff who participated in the study, 204 (73%) completed the questionnaire. The mean score reported for entrepreneurial behavior was 3.76±0.55 considered high tendency toward entrepreneurship. Moreover, the average conditions of the structural elements have been 2.51±0.89 considered average. Linear regression analysis showed that along with increasing age, entrepreneurship behavior increased (P=0.018, β=0.52), while an increase in educational level led to a decrease in entrepreneurship behaviour (P=0.001, β=-0.74). In a final model, organizational structure revealed a significant effect on entrepreneurship behavior (P<0.001, β=0.25). Only physical facilities didn't show a statistical significant effect on entrepreneurship score (P>0.05). Conclusion: Universities must also pay attention to acquiring and developing the science and technology gained from academic research and transferring them through entrepreneurship channels. Considering the effect of structural elements on entrepreneurial behavior of the academic members, the need for such substructure in the universities and the country's higher education organizations to assist development of entrepreneurial behavior among the academicians is greatly felt.